Best approach in crime detection investigation and intelligence - Garcia, Mario B. (Quezon City : Wisemans Books Trading, 2020)
"This book (3z(BBest Approach in Criminal Investigation and Intelligence and Secret Service(3y (Bis the first of a series of author. This book has been written in the hope that this humble work will be of great help to the Criminology students, law enforcement practitioners and aspiring police investigators and police intelligence."s
Includes Bibliographical references.
English Text
Keywords: Criminal investigation Criminals -- Identification Detectives